Lobbying and political polarization - Heinrich W. Ursprung (Hamburg Institute of International Economics (HWWA), 2002)
Standard spatial models of political competition give rise to equilibria in which the competing political parties or candidates converge to a common position. In this paper I show how political polarization can be generated in models that focus on the nexus between pre-election interest group lobbying and electoral competition.
Keywords: D72; 330; political competition; lobbying; interest groups; campaign contributions; Ökonomische Theorie der Demokratie; Interessenpolitik; Wahlkampffinanzierung; Theorie